Implementation of Clinical Pathways and Its Impact on Average Length of Stay (ALOS) in Major Surgery Cases: A Secondary Data Analysis of BPJS Kesehatan Claims - Siti Amallia (Journal of Health Service Administration and Hospital Management, 2026)
The adoption of the Indonesia Case-Base Groups (INA-CBGs) framework mandates a fundamental shift toward hospital operational optimization through standardized medical protocols. This investigation explores the empirical influence of Clinical Pathway (CP) integration on the Average Length of Stay (ALOS) for major surgical interventions within the National Health Insurance (JKN) ecosystem. Purpose: This study aims to quantify the relationship between protocol adherence and inpatient duration while elucidating its role in systemic cost-containment. Methods: Utilizing a quantitative explanatory design, the research analyzed the 2024 BPJS Kesehatan Sample Dataset, comprising 245,672 verified surgical claim entries from diverse hospital classifications across Indonesia. The methodology employed a stratified random sampling approach, utilizing multivariate regression and Pearson correlation analyses to examine clinical compliance indices, demographic determinants, and procedural outcomes relative to National Guidelines (PNPK). Results: The empirical data demonstrates a compelling negative correlation between protocol compliance and hospitalization duration (; ), yielding a comprehensive 33.8% reduction in national ALOS. The most pronounced efficiencies were documented in complex orthopedic procedures (38.1%) and high-risk Cesarean sections (40.4%), generating an average fiscal saving of IDR 4.4 million per encounter. Implications: These results position standardized clinical trajectories as essential deterministic instruments for ensuring fiscal solvency and maximizing bed turnover rates. Conclusion: Stringent CP adherence effectively curtails unwarranted service variability and alleviates financial pressures on social security funds. Future inquiries should synthesize administrative datasets with longitudinal patient-reported outcomes to validate that accelerated discharge protocols do not diminish post-surgical health quality.